Impulse Source in the Vicinity of a Convex Impedance Body: Minimization of the Field in the Shadow Region - Zvyagintsev, A.A.; Ivanov, A.I.; Katkov, D.V. (Радиофизика и радиоастрономия, 2002)
The work deals with the optimization problem of impulse source field minimization in the shadow region of a convex body with variable surface impedance. The optimal impedance is searched using uniform asymptotic methods and Ritz method for functional minimization. Numerical results are presented for the Gaussian impulse source.